The effect of gestational diabetes on human umbilical mesenchymal stem cells and their ability to influence endothelial permeability - Salem, Samar (2023)
Gestational diabetes mellitus (GDM) is associated with short-term adverse complications, such as macrosomia and postnatal fetal hypoglycaemia and long-term metabolic and cardiovascular health consequences for offspring. Placental pathophysiology in gestational diabetes which includes increased insulin resistance and glucose transporters expression, glucose transfer to the fetus, inflammation, and fetoplacental endothelial dysfunction, suggests that GDM may also have an impact on the fetal stem cells from the cord. Therefore, this study aimed to investigate the influence of GDM and its treatment either diet or metformin on Wharton's Jelly Mesenchymal Stem Cells (WJ-MSCs). WJ-MSCs were isolated from term human umbilical cords (n=35) after elective caesarean sections, from normal pregnancies (nWJ-MSCs) (n=13) and those complicated by GDM (gWJ-MSCs) (n=22); either diet-controlled, (d- GDM) and metformin-treated (m-GDM). The effect of GDM on the migratory and secretory properties, doubling time, and cell morphology of WJ-MSCs was investigated. The number of migrated cells from each cord piece was recorded after 7 days. The concentration of VEGF-A in culture supernatant per 1x106 cells was quantified by ELISA. A phenotypic profile for the expression of mesenchymal and hematopoietic markers in gWJ-MSCs using flow cytometry was performed. PKH-26-labelled nWJ-MSC or gWJ-MSCs were added to confluent monolayers of isolated human umbilical vein endothelial cells (HUVEC) and transendothelial migration of the gWJ-MSCs and their effect on endothelial VE-cadherin junctional occupancy were assessed by selective random sampling. nWJ- MSCs or gWJ-MSCs were added on a confluent HUVEC monolayer growing on transwell inserts to investigate tracer leakage across the endothelial monolayer. Statistical comparisons between two groups were performed by independent samples t-test, and among the three groups by One-Way ANOVA, and p-value ≤ 0.05 was considered statistically significant. Compared with nWJ-MSCs, gWJ-MSCs showed a 65 % increase in the number of migrated cells from each cord piece (p <0.005). The concentration of VEGF-A on culture supernatant secreted from gWJ-MSCs was 3.8-fold higher than nWJ-MSCs (p <0.001). On sub-culturing gWJ-MSCs displayed a 20% less elongated spindle shape. gWJ-MSCs were positive for CD-44, CD- 90, CD-105 & CD-73, and negative for CD-14, CD-19& HLA-DR. However, they displayed 17 % higher CD-105 (Endoglin) (ENG) expression (p <0.05). On co-culture with HUVEC, gWJ-MSCs could transmigrate to the sub- endothelium, open the endothelial junctions (observed in significantly reduced VE-cadherin at 2h co-culture time), and resume the junctional occupancy (observed in the VE-cadherin junctional expression at 24h co-culture time), but junctional VE-cadherin counts were 28 % less in the co-cultures HUVEC+ gWJ-MSCs compared to HUVEC+ nWJ-MSCs (p <0.05). The permeability studies revealed that nWJ-MSCs when co-cultured on top of the HUVEC monolayer enhanced the endothelial barrier integrity and decreased the tracer leakage after transmigration to the sub-endothelial niche. However, gWJ- MSCs did not do so evidenced by increased tracer leakage concentration by 19% compared to nWJ-MSCs. Endoglin silencing in WJ-MSCs after ENG siRNAs transfection was done to investigate whether the compromised ability of gWJ-MSCs to tighten the endothelial barrier when co-cultured with HUVEC and the increased permeability is via an ENG-dependent mechanism. WJ-MSCs from normal pregnancy were transfected with ENG siRNAs, and gene knockdown was confirmed at the protein level by flow cytometry. The effect of ENG silencing on the VEGF secretion by WJ-MSCs was assessed by ELISA. Permeability assay and immunocytochemistry localization of VE-cadherin at the endothelial junctions after co-culturing with either silenced WJ-MSCs (ENG-/-) or non- silenced WJ-MSCs (ENG+/+) were performed. The concentration of VEGF-A secreted in culture from WJ-MSCs was doubled after ENG silencing (p ≤0.0001). ENG loss in WJ-MSCs reduced the stem cell attachment to the endothelial monolayer by 53%. Loss of ENG in WJ-MSCs can impair the ability of the stem cell to maintain the endothelial barrier integrity observed in increased tracer leakage concentration in the co- culture HUVEC + ENG-/-WJ-MSCs (p ≤ 0.05) and reduced number of junctions displaying continuous VE-cadherin expression by 75.33% compared to the non-silenced cells HUVEC + ENG+/+WJ-MSCs. These changes in vascular permeability, even in well-controlled gestational diabetes, suggest an impaired ability of gWJ-MSC, to maintain/increase endothelial integrity after transmigration. However, the differences found in the comparison between the fetal mesenchymal stem cells from GDM-complicated pregnancy and normal pregnancy elucidate the need to do more investigations on the pathogenesis of GDM. ENG mediates multiple endothelial cell responses in response to angiogenic signals from VEGF, and its loss in stem cells leads to increased VEGF-A secretion, reduced stem cell attachment, and deteriorating effect on the endothelial barrier integrity, thus its role in GDM needs to be further investigated.